СУЧАСНІ НАДВИСОКОВОЛЬТНІ КАБЕЛІ З ІЗОЛЯЦІЄЮ ЗІ ЗШИТОГО ПОЛІЕТИЛЕНУ (ОСОБЛИВОСТІ І ТЕНДЕНЦІЇ РОЗВИТКУ) - Кучерява, І.М. (Інститут електродинаміки Національної академії наук України, 2025)
The paper presents and analyzes the basic advantages and trends in the development and application of extra-high-voltage cables with cross-linked polyethylene insulation. Due to their ability to support the integration with renewable energy sources and fiber-optic technologies, increase the network efficiency, reduce the transmission losses, as well as owing to the achievements and new technologies in designs and improvements in insulation materials, these cables play a significant role in the development of the world's energy industry and the creation of future energy infrastructure. Ref. 31, fig. 3, tables 3.